Pre-Project Selling in a Property Business: The Perspective of Islamic Law - Agus Sekarmadji; Regine Wiranata; Oemar Moechthar (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2021)
Actors in the real estate market have developed a marketing strategy in the form of pre-project selling. This strategy is conducted to perform a market test for any property a developer intends to market. However, in practice, the system often poses problems, such as misrepresenting the property and inflicting customers' financial losses. From the perspective of Islamic law, this type of transaction is characterized as gharar (uncertainty, deception, and risk), having no exact object, and having forbidden. This article uses a Sharia-based perspective to analyze the characteristics of pre-project selling. This research aims to determine the legality of pre-project selling under Sharia law and prescribe solutions for society. The method used in this article is legal research, using legislation-based, conceptual, and case-based approaches, along with a comparison of national legislation with the written text of the al-Qur’an and hadith. The paper concludes that while pre-project selling should not be legally banned, there need steps taken to reduce its risks. This could be applied, for example, by creating minimum prerequisites for allowing pre-project selling, such as the existence of a plot for construction or the requirement of permits to be obtained before the pre-project sale. This research contributes to the development of legal science in general and Islamic jurisprudence, especially regarding Islamic law agreements' validity.